Phosphate fertilization and organic compost on the initial growth of sorghum in degraded soils - Cardoso, Edvaldo Renner da Costa; Silva, Francisco Nildo da; Maia, Sandra Sely Silveira; Hernandez, Fernando Felipe Ferreyra; Santos, Rosemery Alesandra Firmino dos; Nazareno, Lailla Sabrina Queiroz (Scientia Agraria Paranaensis, 2020)
One of the strategies for the recovery of degraded soils is the planting of fast-growing forage species with high biomass production. In this sense, the objective of this research was to evaluate the initial growth of sorghum in degraded soils with organic fertilization and different phosphorus levels. A completely randomized design with a 4 x 3 x 2 factorial arrangement was used, with four soil types, three levels of phosphorus fertilization and two levels of organic fertilization. At 64 days after sowing the characteristics of the initial growth were analyzed: plant height, stem diameter, leaf number and fresh shoot mass. The height was measured by measuring the neck of the plant until the end of the newest fully expanded leaf, measured with the aid of a measuring tape and expressed in centimeters. The diameter of the stem, by means of a digital pachymeter. The application of phosphorus and organic matter in degraded soils is necessary for the initial development of sorghum plants, due to the low availability of this element, caused by the high adsorption of P in the soil colloids. Besides that, the lack of organic matter in the studied soils led to a decrease in the growth of sorghum, therefore, it is concluded that soil management in saline environments is necessary for the application of phosphorus and organic matter for a sustainable and technically viable production.